Kedudukan Hukum PT Maspion Dalam Sengketa Perpanjangan Hak Guna Bangunan (HGB) di Atas Hak Pengelolaan (HPL) (Kasus Surabaya): Perspektif Kepastian Hukum dan Perlindungan Hak - Rabiah, Salwa; Fedira, Revania; Sedyo, Nastiti Respati; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the legal status of Building Use Rights (HGB) over Management Rights (HPL) and its implications for legal certainty in Indonesia’s agrarian system through the case analysis of PT Maspion vs. Surabaya City Government. HGB over HPL is a derivative right dependent on the HPL holder’s authority but remains an independent right with economic value. The differing rulings between the Administrative Court and the Supreme Court reveal inconsistencies in legal interpretation, creating uncertainty for rights holders. Therefore, clearer and more comprehensive regulations on the extension mechanism of HGB over HPL are needed to ensure legal protection, fairness, and investment stability in land law.